Geographical and environmental epidemiology methods for small area studies - Elliott, P. (Paul) (Oxford : Oxford University Press, 1996)
Requirements in terms of population data, disease incidence and mortality are considered and related to the scale at which a study is being carried out. Statistical methods are reviewed for large scale correlation studies, intermediate scale smoothing excercises, and small-scale clustering investigations, plus much more.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology; Human geography; Human ecology